2022
DOI: 10.3390/nu14091954
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Drinking Pattern, and Chronic Disease

Abstract: This review discusses the inconsistent recommendations on alcohol consumption and its association with chronic disease, highlighting the need for an evidence-based consensus. Alcohol is an addictive substance consumed worldwide, especially in European countries. Recommendations on alcohol consumption are controversial. On one hand, many nonrandomized studies defend that moderate consumption has a beneficial cardiovascular effect or a lower risk of all-cause mortality. On the other hand, alcohol is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 153 publications
1
23
0
1
Order By: Relevance
“…And equally expected was the lower risk of dying among those who were in the highest quintiles of social class, whose effect cannot be explained by lifestyle factors such as smoking, diet or physical activity 23 . The protective effect found for moderate consumption of alcohol in the general population has been previously described 24 and is controversial 25 . On the other hand, for being overweight and obesity, there was the paradoxical protective association with mortality that has been described previously 26 , and the controversy surrounding it has been debated 27 .…”
Section: Discussionmentioning
confidence: 91%
“…And equally expected was the lower risk of dying among those who were in the highest quintiles of social class, whose effect cannot be explained by lifestyle factors such as smoking, diet or physical activity 23 . The protective effect found for moderate consumption of alcohol in the general population has been previously described 24 and is controversial 25 . On the other hand, for being overweight and obesity, there was the paradoxical protective association with mortality that has been described previously 26 , and the controversy surrounding it has been debated 27 .…”
Section: Discussionmentioning
confidence: 91%
“…However, by comparing different ALD models, we found that in models only using an LDE diet, the main changes in animals were limited to early ALD (hepatic steatosis and inflammation), while those of more severe ALD (such as hepatitis and fibrosis) were rarely able to be observed [ 112 ]. Alcohol, as a susceptibility factor for many diseases, can affect the progression of the disease, and in many cases, this effect is only clinically relevant after secondary injury [ 13 , 202 ]. When the liver is damaged, alcohol drinkers are more likely to develop fibrosis and cirrhosis [ 203 , 204 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on current findings it is possible that the patterns of drinking and beverage-specific differences may also explain previous observations on the dose–response relationships between alcohol consumption and attributable health outcomes [ 1 , 9 ]. Several lines of evidence have suggested that drinking wine in light to moderate amounts may be associated with good benefits of cardiovascular health [ 19 , 21 , 27 , 28 , 29 ]. However, such findings have been reported primarily from samples representing societies with a low prevalence of binge drinking and populations following Mediterranean diets.…”
Section: Discussionmentioning
confidence: 99%
“…The present observations also support the view that a wide variety of lifestyle-related risk factors and their combinations may play a significant role in the metabolic consequences of alcohol intake in individuals with different alcohol drinking patterns and preference types. Previous studies have suggested that wine drinkers typically drink together with meals and also consume more vegetables [ 27 , 29 ]. The present data among male participants indicate a higher number of physical exercises in wine drinkers than in those preferring other types of alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%